PENGARUH KEAHLIAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT MITRA FESYEN GLOBAL DI KOTA TANGERANG - Azis, Mochamad Basit; Savitri, Shela Indah (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work skills and organizational culture on employee performance at PT Mitra Fesyen Global in Tangerang City, both partially and simultaneously. This type of research uses quantitative methods with a sampling technique using saturated sampling which was used by 66 respondents. The analysis techniques used are data instrument tests, classical assumption tests, regression analysis, coefficient of determination analysis, and hypothesis testing (t test and f test). Based on research results, Job Skills have a significant effect on Employee Performance with a correlation coefficient value of 58.5% and hypothesis testing obtained a calculated t value > t table or (5.301 > 1.998). Organizational culture has a significant effect on employee performance with a correlation coefficient value of 57.6% and the hypothesis test obtained a calculated t value > t table or (5.109 > 1.998). Work Skills and Organizational Culture partially and simultaneously have a significant effect on Employee Performance with the regression equation Y = 3.572 + 0.707 X1 + 0.546 . Hypothesis testing obtained F count > F table or (75.857 > 3.14).